Evaluation of Compliance of Domestic Waste Management to Environmental Quality Standard At the Implementation Unit of PT PLN (Persero) East Java and Bali Transmission - Dinatha, Nabila Putri; Murti, Restu Hikmah Ayu (International Journal of Eco-Innovation in Science and Engineering (IJEISE), 2025)
Domestic waste management in accordance with environmental quality standards is an important part of maintaining environmental quality and supporting the sustainability of company operations. This study aims to describe the level of compliance of domestic waste management at the Transmission Unit of PT PLN (Persero) East Java and Bali to applicable environmental quality standards, especially those regulated in Government Regulations and Regulations of the Minister of Environment. This study aims to evaluate the extent to which PLN's domestic waste management practices comply with the established environmental quality standards. This study uses a descriptive method with a qualitative approach, involving field observation and review of RKL-RPL documents of the Implementing Unit of PT. PLN East Java and Bali Transmission Main Unit. Data collection includes direct observation of the domestic waste processing process, and analysis of environmental monitoring reports. Parameters such as Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), pH, Total Suspended Solids (TSS), Lead (Pb) and oil and fat are analyzed to assess compliance with applicable environmental regulations. The results of the study indicate that most domestic waste management activities have complied with the established standards, although there are still some weaknesses in the aspects of recording, monitoring wastewater quality, and the availability of supporting facilities. These findings provide a basis for recommendations for improving internal supervision and improving the company's environmental management system.